Pipeline embolization device retraction and foreshortening after internal carotid artery blister aneurysm treatment. Issue 6 (December 2017) - Heit, Jeremy J; Telischak, Nicholas A; Do, Huy M; Dodd, Robert L; Steinberg, Gary K; Marks, Michael P
Background: Subarachnoid hemorrhage (SAH) secondary to rupture of a blister aneurysm (BA) results in high morbidity and mortality. Endovascular treatment with the pipeline embolization device (PED) has been described as a new treatment strategy for these lesions. We present the first reported case of PED retraction and foreshortening after treatment of a ruptured internal carotid artery (ICA) BA. Case description: A middle-aged patient presented with SAH secondary to ICA BA rupture. The patient was treated with telescoping PED placement across the BA. After 5 days from treatment, the patient developed a new SAH due to re-rupture of the BA. Digital subtraction angiography revealed an increase in caliber of the supraclinoid ICA with associated retraction and foreshortening of the PED that resulted in aneurysm uncovering and growth. Conclusions: PED should be oversized during ruptured BA treatment to prevent device retraction and aneurysm regrowth. Frequent imaging follow up after BA treatment with PED is warranted to ensure aneurysm occlusion.